The Influence of Accounts Receivable Turnover and Inventory Turnover on Profitability at PT Sumber Alfaria Trijaya Tbk - Amthy Suraya (Universitas Negeri Makassar, 2018)
The sales process at a distribution or retail company cannot be separated from the influence of the inventory held by the company. This study aims to analyze the effect of Accounts Receivable Turnover and Inventory Turnover on Return on Assets (ROA) of the company. The data used in this study are secondary data sourced from financial data on the Indonesia Stock Exchange contained in the company's financial statements. This research was conducted at PT Sumber Alfaria Trijaya Tbk in the period 2011-2017. The statistical analysis used in this study is the classic assumption test, multiple linear regression, coefficient of determination, and hypothesis testing using the t-test and f test. Partially (t-test) obtained receivables turnover (X1) has no effect but is not significant on Return on Assets (ROA), while inventory turnover (X2) has an effect but not significantly on Return on Assets (ROA) (Y). Simultaneously (test f) obtained Receivables Turnover (X1) and inventory turnover (X2) have a significant effect on Return On Assets (ROA). Based on the results of R2 the independent variable Accounts receivable turnover and inventory turnover have an effect of 80.1% on the dependent variable that is Return on Assets (ROA), while the remaining 19.9%, is influenced by other variables not examined in the study.